2011
DOI: 10.1088/1748-9326/6/3/034024
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the carbon cycle of Amazon ecosystems during the 2010 drought

Abstract: Satellite remote sensing was combined with the NASA-CASA (Carnegie Ames Stanford Approach) carbon cycle simulation model to evaluate the impact of the 2010 drought (July through September) throughout tropical South America. Results indicated that net primary production in Amazon forest areas declined by an average of 7% in 2010 compared to 2008. This represented a loss of vegetation CO 2 uptake and potential Amazon rainforest growth of nearly 0.5 Pg C in 2010. The largest overall decline in ecosystem carbon ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 17 publications
2
35
0
Order By: Relevance
“…The 2009–2010 drought in the Amazon region was one of the most severe in recent history, and water levels in rivers across the basin reached record low levels by October of 2010 (Xu et al., ). Combined with the effects of the relatively low NPP, which were also caused by drought (Potter, Klooster, Hiatt, Genovese, & Castilla‐Rubio, ), the wetland CH 4 emissions declined significantly in the Amazon Basin and result in a drop in total wetland CH 4 emissions from the entire tropical area.…”
Section: Discussionmentioning
confidence: 99%
“…The 2009–2010 drought in the Amazon region was one of the most severe in recent history, and water levels in rivers across the basin reached record low levels by October of 2010 (Xu et al., ). Combined with the effects of the relatively low NPP, which were also caused by drought (Potter, Klooster, Hiatt, Genovese, & Castilla‐Rubio, ), the wetland CH 4 emissions declined significantly in the Amazon Basin and result in a drop in total wetland CH 4 emissions from the entire tropical area.…”
Section: Discussionmentioning
confidence: 99%
“…Models and remote sensing are effective tools for assessing how terrestrial carbon cycles respond to droughts on both regional and global scales (Chen et al, 2012a). Several modeling studies have recently been conducted to assess the impact of droughts on the productivity and carbon budget of terrestrial ecosystems for western North America (Schwalm et al, 2012), the southern United States (Chen et al, 2012a), Europe (Ciais et al, 2005;Vetter et al, 2008), Amazonia (Phillips et al, 2009;Potter et al, 2011;Nunes et al, 2012), East Asia Xiao et al, 2009), the Northern Hemisphere mid-latitudes (Zeng et al, 2005), and the globe Chen et al, 2013). All these studies indicated that droughts significantly influence the terrestrial carbon cycle and might even cause terrestrial ecosystems to shift from carbon sinks to carbon sources Ponce Campos et al, 2013;Piao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Climate models suggest increased drought frequency and intensity under some climate change scenarios (Hutyra et al, 2005;Malhi et al, 2008), but these predictions are limited by uncertainties in forecasting rainfall patterns over tropical South America (Marengo et al, 2012). Possible impacts of recurrent droughts over upland Amazonian forests have been addressed (Saleska et al, 2007;Phillips et al, 2009;Lewis et al, 2011;Potter et al, 2011), but little attention has been given to the effects of increased drought intensity and frequency on the aquatic ecosystems of the Amazon floodplains, and especially on herbaceous vegetation (Melack & Coe, 2013).…”
Section: Introductionmentioning
confidence: 99%